Skeletal Muscle Repair and Regeneration: Focusing on The Role of Satellite Cells and Myogenic Regulatory Networks - Kakhai, Chanrit; Yamprayoon, Phornnabphan; Chanvorachot, Pithi (Journal of Physiological and Biomedical Sciences, 2025)
Understanding the mechanisms of skeletal muscle regeneration is crucial for advancing therapeutic strategies to manage muscle injuries and prevent muscle-related degenerative diseases. Skeletal muscle regeneration is a tightly regulated process involving structural, cellular, and molecular components. which provide mechanical stability and facilitate vascular and neural integration. Muscle fibers are multinucleated and contain organized myofibrils composed of actin and myosin, enabling contraction. In addition, muscle stem cells, known as satellite cells, are essential for muscle regeneration, and the balance between their quiescent and activated states has been widely investigated in regenerative biology. Upon activation, satellite cells exit quiescence, proliferate, differentiate into myoblasts, and fuse to form new myofibers. This regenerative process proceeds through three distinct stages: destruction, repair, and remodeling, coordinated by immune cells, cytokines, and growth factors. Transcription factors such as Pax7, MyoD, and MyoG play critical roles in regulating myogenesis. Effective muscle regeneration relies on the dynamic interplay between satellite cells, fibroblasts, and extracellular matrix remodeling to restore functional integrity.